A phase-change material with high through-plane thermal conductivity comprising a palmitic acid–cellulose nanofiber matrix with via acylation an expanded graphite@cellulose nanofiber@carbon nanotube hybrid filler. (15th January 2023) - Yang, Wonyoung; Kim, Jooheon
Abstract: Although phase-change materials (PCMs) are promising candidates for thermal storage applications due to their high latent heat during phase transition, challenges such as the leakage problem during phase transition and low thermal conductivity must be overcome. We fabricated a palmitic acid (PA)–cellulose nanofiber (CNF) matrix via acylation and a hybrid expanded graphite (EG)@CNF@carbon nanotube (CNT) filler via grafting of CNFs onto the surface of the EG. The matrix and hybrid filler mixture were then hot-pressed to provide an efficient heat pathway. The fabricated composite with 7 wt% hybrid filler reached through-plane thermal conductivity of 1.98 W/mK and latent heat of 102.04 J/g. Especially, the fabricated composite showed 3.4 times higher thermal conductivity enhancement compared to raw PA-CNF. Furthermore, the composite is lightweight and flexible. Based on these findings, the manufactured composite possesses the potential as a PCM for thermal energy storage and thermal management applications. Highlights: The EG@CNF@CNT hybrid filler was fabricated by grafting CNF with oxalic acid. The PA-CNF matrix was fabricated with acylation of CNF. The through-plane thermal conductivity and latent heat were 1.98 W/mK and 102.04 J/g.